The Dynamics of Impulse Buying: Exploring the Impact of Price Discounts, Time Pressure, Easy of Transaction, and Price Perception on Shopee Live - Oning Amasuba, Agnes; Apriani, Ari (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study investigates the factors influencing impulse buying behavior on Shopee Live, focusing on price discounts, time pressure, ease of transaction, and price perception. The findings reveal that price discounts significantly and positively affect impulse buying. Discounts enhance the perceived value of products, create a sense of urgency with time-limited offers, and utilize social influence by showcasing other buyers taking advantage of the deals. Time pressure also plays a crucial role, as it intensifies urgency, leading consumers to make quick, impulsive decisions. The interaction between sellers and consumers during live streaming further amplifies this effect. Conversely, ease of transaction does not significantly impact impulse buying. Although a smooth transaction process is appreciated, it does not independently drive impulsive purchases without the presence of other motivating factors. Additionally, positive price perception significantly boosts impulse buying, as consumers who view prices favorably are more likely to make spontaneous purchases. This study underscores the effectiveness of price discounts, time pressure, and positive price perception in enhancing impulse buying on Shopee Live, suggesting that sellers can optimize these factors to increase sales.